Macro and micro challenges for talent retention in South Africa - Berenice Kerr-Phillips; Adèle Thomas (SA Journal of Human Resource Management, 2009)
The aim of the study was to explore the challenges presented in retaining South Africa’s talent at both macro (country) and micro (organisational) levels. Using a web-based survey placed on eight New Zealand sites, the reasons for emigration of South African talent during the period 1994–2006 were explored with 84 respondents. Utilising a purposive sampling technique, 20 semi-structured interviews were undertaken with identified ‘top talent’ in two financial services companies. Content analysis of the responses from both samples was employed. Reasons for emigration (macro issues) included uncertainty about the future of the country, job insecurity and fears regarding both corruption and violent crime. Reasons for talent loss amongst identified top talent (micro issues) were found to be linked to leadership, organisational culture and employment equity.